Herbal Medicines as Complementary Therapy for Managing Complications in COVID-19 Patients with Diabetes Mellitus - Adha SA; Afifah NN; Latarissa IR; Iftinan GN; Kusuma ASW; Febriyanti RM; Barliana MI; Lestari K (Diabetes, Metabolic Syndrome and Obesity)
Syah Akbarul Adha,1 Nadiya Nurul Afifah,1,2 Irma Rahayu Latarissa,3,4 Ghina Nadhifah Iftinan,4 Arif Satria Wira Kusuma,1,2 Raden Maya Febriyanti,1 Melisa Intan Barliana,1,2 Keri Lestari2– 4 1Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 2Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, Indonesia; 3Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, Indonesia; 4Medication Therapy Adherence Clinic (MTAC), Universitas Padjadjaran, Sumedang, IndonesiaCorrespondence: Keri Lestari, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM. 21, Jatinangor, 45363, Indonesia, Email lestarikd@unpad.ac.idAbstract: Diabetes mellitus (DM) is recognized and classified as a group of conditions marked by persistent high blood glucose levels. It is also an inflammatory condition that may influence concurrent disease states, including Coronavirus Disease 2019 (COVID-19). Currently, no effective drug has been found to treat COVID-19, especially in DM patients. Many herbal medicines, such as the well-known Andrographis paniculata, have been explored as drugs and complementary therapies due to their antidiabetic, antibacterial, antiviral, anti-inflammatory, and immunomodulatory effects. This study aimed to examine the potential of herbal medicines as complementary therapy in DM patients with COVID-19 complications, drawing from in-vitro and in-vivo investigations. This study analyzed articles published within the last 15 years using keywords including “herbal medicines”, “COVID-19”, “Diabetes Mellitus”, “antidiabetics”, “antiviral”, and “anti-inflammatory”. The results showed that several herbal medicines could serve as complementary therapy for DM patients with COVID-19 complications. These include Andrographis paniculata, Ageratum conyzoides, Artocarpus altilis, Centella asiatica, Momordica charantia, Persea gratissima, Phyllanthus urinaria, Physalis angulata, Tinospora cordifolia, and Zingiber zerumbet. Herbal medicines may serve as a complementary therapy for DM patients with COVID-19, but these claims need experimental validation in infection models and among affected patients.Keywords: COVID-19, diabetes mellitus, antidiabetic, immunomodulator, anti-inflammatory, herbal medicines